Bacterial infections and patterns of antibiotic use in patients with COVID‐19. Issue 3 (28th September 2020) - Goncalves Mendes Neto, Alvaro; Lo, Kevin Bryan; Wattoo, Ammaar; Salacup, Grace; Pelayo, Jerald; DeJoy, Robert; Bhargav, Ruchika; Gul, Fahad; Peterson, Eric; Albano, Jeri; Patarroyo‐Aponte, Gabriel; Rangaswami, Janani; et al.
Abstract: Bacterial coinfection is associated with poor outcomes in patients with viral pneumonia, but data on its role in the mortality of patients with coronavirus disease 2019 (COVID‐19) is limited. This is a single‐center retrospective analysis of 242 patients with confirmed COVID‐19 admitted to both intensive care and non‐intensive care settings. Bacterial coinfection was determined by the presence of characteristic clinical features and positive culture results. Multivariable logistic regression was used to analyze the association of concomitant bacterial infection with inpatient death after adjusting for demographic factors and comorbidities. Antibiotic use pattern was also determined. Bacterial coinfection was detected in 46 (19%) patients. Genitourinary source was the most frequent, representing 57% of all coinfections. The overall mortality rate was 21%. Concomitant bacterial infections were independently associated with increased inpatient mortality (OR, 5.838; 95% CI, 2.647‐12.876). Patients with bacterial coinfection were relatively older (71.35 ± 11.20 vs 64.78 ± 15.23; P =  .006). A total of 67% of patients received antibiotic therapy, yet 72% did not have an obvious source of bacterial infection. There was a significantly higher rate of inpatient mortality in patients who received antibiotics compared to those who did not (30% vs 5%; P  < .0001). Bacterial coinfection in COVID‐19 is associated with increased mortality. Highlights: Concomitant bacterial infections were independently associated with increased inpatient mortality. Patients placed on antibiotics had poorer outcomes and higher inflammatory markers. The presence of coinfection may not be causative of worse clinical outcomes but rather signify clinical deterioration.